Commit c148ac4d authored by Robbert Krebbers's avatar Robbert Krebbers
Browse files

Prove `E2 ⊆ E1 → P ={E1,E2}=∗ P`.

parent b33a29de
......@@ -203,6 +203,13 @@ Section fupd_derived.
Lemma fupd_wand_r E1 E2 P Q : (|={E1,E2}=> P) (P - Q) ={E1,E2}= Q.
Proof. by rewrite fupd_frame_r wand_elim_r. Qed.
Lemma fupd_mask_weaken E1 E2 P `{!Absorbing P} : E2 E1 P ={E1,E2}= P.
intros ?. rewrite -{1}(right_id emp%I bi_sep P%I).
rewrite (fupd_intro_mask E1 E2 emp%I) //.
by rewrite fupd_frame_l sep_elim_l.
Lemma fupd_trans_frame E1 E2 E3 P Q :
((Q ={E2,E3}= emp) |={E1,E2}=> (Q P)) ={E1,E3}= P.
Supports Markdown
0% or .
You are about to add 0 people to the discussion. Proceed with caution.
Finish editing this message first!
Please register or to comment